Whether Top Executives’ Turnover Influences Environmental Responsibility: From the Perspective of Environmental Information Disclosure - Meng, X. H.; Zeng, Saixing; Tam, Chiming; Xu, X. D. (2013)
We have empirically examined the relationship between top executives’ turnover and the corporate environmental responsibility by identifying the influence of ten specific turnover reasons resulting in the chairman’s departure and two important types of chairman’s succession. Using a sample of 782 manufacturing listed companies across 3 years in China, we find that the corporate environmental responsibility is negatively associated with the involuntary and negative turnover (i.e., dismissal, health and death, and forced resignation) and positively associated with improving corporate governance, and not associated with the normal turnover (i.e., retirement and contract expiration) and the types of chairman’s succession (i.e., independence, and internal or external promotion). Our study significantly contributes to research in environmental disclosure by revealing the relationship between chairman’s turnover and the corporate environmental responsibility. A feasible way is suggested to regulators and other stakeholders in monitoring or assessing the possible abnormality of environmental responsibility when firms experience involuntary and negative chairman’s turnover in the emerging economies.
Keywords: Turnover; Top executive; environmental information; Environmental Responsibility